Praktik Adopsi Anak di Masyarakat Bugis: Antara Pandangan Ulama dan Budaya - Yusuf, Muhammad; Wekke, Ismail Suardi (al-'adalah, 2018)
This article reviews the tradition of adoption among Bugis people through the views of Bugis scholars and values of local wisdom. This research is a qualitative research using a content analysis approach. The study finds the fact that Bugis scholars have identified two forms of adoption practices. First, the practice of adoption as it is currently happening which change the nasab (lineage) so that it can inherit each other. Second, adoption practices that do not change the nasab. The first model is adoption that is prohibited in Islam in order to maintain the law and the descent according to the intentions of cultural values of paccing and sticking. The second model is allowed adoption. Such adoption practices are even encouraged if the motives are humanitarian motives and also in accordance with the values of the pesse culture (pacce), namely a deep sense of humanity and sibaliperri (mutual cooperation spirit).